Circulating Cell-Free DNA in Hepatocellular Carcinoma: Current Insights and Outlook - Ng, Charlotte K. Y.; Di Costanzo, Giovan Giuseppe; Terracciano, Luigi M.; Piscuoglio, Salvatore (Frontiers in Medicine, 2018)
Over the past decade, the advancements in massively parallel sequencing have provided a new paradigm in biomedical research to uncover the genetic basis of human diseases. Integration of ‘omics information has begun transforming clinical management of cancer patients in terms of diagnostics and treatment options, giving rise to the era of precision medicine. Currently, nucleic acids for molecular profiling for patients diagnosed with hepatocellular carcinoma are typically obtained from resected tumor materials or transplanted neoplastic liver, and occasionally, from biopsies. Given the intrinsic risks associated with such invasive procedures, circulating cell-free DNA (cfDNA) has been proposed as an alternative source for tumor DNA. Circulating cfDNA is a type of cell-free nucleic acid that derives from apoptotic, necrotic, as well as living eukaryotic cells. Importantly, the detection of abnormal forms of circulating cfDNA that originate from cancer cells provides a new tool for the cancer detection, disease monitoring and molecular profiling. Currently, cfDNA is beginning to be adopted into clinical practice as a non-invasive tool to monitor disease by tracking the evolution of disease-specific genetic alterations in several major cancer types. Moreover, cfDNA is demonstrating potential clinical value as a surrogate to assess the molecular makeup of tumors and to overcome the sampling biases inherent to intra-tumor genetic heterogeneity, especially in the metastatic setting. With the improvements in ‘omics and molecular biology techniques, coupled with the increasing understanding in the molecular pathogenesis of cancer, it can be anticipated that the detection and analysis of cfDNA will become more specific and sensitive and thus enable cfDNA analysis to be used as a diagnostic aid in patients with early-stage disease, and perhaps, even in a screening setting. In this review, we provide an overview of the latest findings on the role and potential utility of cfDNA analysis in the diagnosis, management and screening of hepatocellular carcinoma.